Improved extension practices for sheep and beef farmers - Gray, DI; Sewell, AM; Hartnett, M; Wood, BA; Kemp, PD; Blair, HT; Kenyon, PR; Morris, ST (New Zealand Grassland Association Occasional Publication)
Innovation is critical for maintaining New Zealand’s competitive advantage in agriculture and central to this is farmer learning and practice change. Despite the importance of farmer learning, limited research has been undertaken in New Zealand. In this study, an extension programme was developed based upon educational theory and research and then evaluated over a 3 years to identify the factors that were important for farmer learning and practice change. This paper provides a brief overview of findings of a 3 year interdisciplinary study conducted at Massey University with 23 farmers that investigated the critical factors that support farmers’ learning. The five critical success factors and the seven educational principles identified from this study provide guidelines for how science should interact with farmers to foster effective innovation. These findings are also applicable to other extension approaches such discussion groups, monitor farms and sustainable farming fund initiatives where farmers work with scientists and/or rural professionals.
Keywords: farmer learning; extension; practice change; herb pastures; innovation; community of practice